Determination green human resource management: Analysis green training, green behavior, green leadership, and green organizational culture (study literature review) - Febrian, Wenny Desty (Goodwood Publishing, 2025)
Purpose: The purpose of this study is to develop hypotheses related to factors that influence green human resource management, especially in the campus environment/world of education. Methodology: The approach used in this literature review is descriptive qualitative. The data collection technique is to use literature studies or review previous relevant articles. The data used in this descriptive qualitative approach are derived from previous studies relevant to this research and sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage Q2-Q4, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar, and digital reference books. Results: The results of this literature review are as follows: 1) Green training influences green human resource management; 2) Green behavior influences green human resource management; 3) Green leadership influences green human resource management; and 4) Green organizational culture influences green human resource management. Conclusions: This study concludes that green training, green behavior, green leadership, and green organizational culture significantly influence Green Human Resource Management in higher education, fostering sustainable practices, enhancing HR quality, and strengthening universities’ commitment to green campus initiatives. Limitations: This study is limited to green HRM in the campus/educational setting. Contribution: This study contributes to the understanding of factors influencing green HRM, focusing on factors such as green training, green behavior, green leadership, and green organizational culture.